China and The Power of A New Economic Hegemony - Nguyen Duc Min (International Journal of Science and Society, 2020)
The result of the break up of the Soviet Union empire in 1990 saw the emergence of China as the sole super power which still clings to the Communist ideology. China thus has the potential of taking over the previously held role of the Soviet Union. The re-emergence of China in the international arena after a long period of isolation may create a great impact on other super powers. China's intention and aspiration to be a new economic hegemonic power not only at regional but also at global levels makes China a country to be reckoned with. The writer will seek to discuss in this article three factors that contribute to China's economic success; firstly, the developments that have taken place in the transformation of China's economic policy from centrally controlled economy to that of the open and free economy as implemented by the Chinese leadership as part of their efforts to generate economic activities and increased competitiveness; secondly, the efforts in safeguarding China's interests in the WTO; and lastly, the role of Hong Kong's and Macau's participation in China's economic development.